2008
DOI: 10.1177/1362361307086662
|View full text |Cite
|
Sign up to set email alerts
|

How central is central coherence?

Abstract: This study aimed to test the assumption drawn from weak central coherence theory that a central cognitive mechanism is responsible for integrating information at both conceptual and perceptual levels. A visual semantic memory task and a face recognition task measuring use of holistic information were administered to 15 children with autism and 16 typically developing children. If there is a central integration mechanism, performance on the two tasks should be positively associated. No relationship was found, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…WCC has been criticized for being overly focused on a deficit at the level of contextual, global processing, while there is also research showing a preference for local processing, with global processing sometimes intact (see e.g., Plaisted et al, 1999; Mottron et al, 2000). The theory is also questioned on the basis of how central the drive for central coherence really is, i.e., whether a deficit in integrated information processing spans all levels of cognitive processing (López et al, 2008).…”
Section: Current Understanding Of Autismmentioning
confidence: 99%
“…WCC has been criticized for being overly focused on a deficit at the level of contextual, global processing, while there is also research showing a preference for local processing, with global processing sometimes intact (see e.g., Plaisted et al, 1999; Mottron et al, 2000). The theory is also questioned on the basis of how central the drive for central coherence really is, i.e., whether a deficit in integrated information processing spans all levels of cognitive processing (López et al, 2008).…”
Section: Current Understanding Of Autismmentioning
confidence: 99%
“…Central coherence, another theory that attempts to explain the social deficit in autism is the ability to integrate information into a coherent whole in perceptual and conceptual level [14]. Seeing a wooden object in a rectangular shape, with a pair of doors with locks and handles, one immediately recognizes it as a closet, as well as eyes, nose and mouth in a particular arrangement is a face.…”
Section: Discussionmentioning
confidence: 99%
“…As for the cognitive processes underpinning text comprehension, a study by Jolliffe and Baron-Cohen (2000) suggested that a crucial ability involved in the construction of a coherent mental representation of the story plot is Central Coherence (CC). CC is a cognitive ability assumed to be responsible for integrating the single elements of an event into a wider global context at both the conceptual (i.e., semantic) and perceptual (i.e., visual) level (Frith, 1989;Happé et al, 2001;López et al, 2008;Plaisted, 2001). In a study by Jolliffe and Baron-Cohen (2000), adults with ASD were administered The Global Integration Test, which requires participants to rearrange sentences describing the single events of a narrative in accordance with a theme to tell the most coherent story.…”
Section: Linguistic and Visual Narrative Comprehension: Processes And...mentioning
confidence: 99%